Dexa-BEAM in patients with Hodgkin's disease refractory to multidrug chemotherapy regimens: a trial of the German Hodgkin's Disease Study Group. - Pfreundschuh, Michael; Rueffer, U.; Lathan, B.; Schmitz, N.; Brosteanu, O.; Hasenclever, D.; Haas, Rainer; Kirchner, H.; Koch, P.; Kuse, R.; Loeffler, Markus; Diehl, Volker (Journal of clinical oncology, 1994)
Purpose - A prospective phase II study was conducted to evaluate the efficacy of dexamethasone, carmustine, etoposide, cytarabine, and melphalan (Dexa-BEAM) as salvage chemotherapy for patients with Hodgkin's disease. - Patients and Methods - Fifty-five patients progressing on or relapsing after eight- or 10-drug chemotherapy (cyclophosphamide, vincristine, procarbazine, and prednisone plus doxorubicin, bleomycin, vinblastine, and dacarbazine [COPP+ABVD] or COPP+ABV+ifosfamide, methotrexate, etoposide, and prednisone [IMEP]) were treated with Dexa-BEAM. Patients who responded after two cycles of Dexa-BEAM either continued treatment for another two to three cycles or received high-dose chemotherapy/autologous bone marrow transplantation (HDCT/ABMT) with cyclophosphamide, etoposide, and carmustine (BCNU) (CVB) as conditioning regimen. - Results - Seventeen patients (31%) achieved a complete remission and 16 (29%) a partial remission, resulting in a response rate of 60% (95% confidence interval, 46% to 73%). Progressive disease developed in 18 patients. Toxicity of Dexa-BEAM was acceptable with pronounced, but temporary World Health Organization (WHO) grade III/IV granulocytopenia and thrombocytopenia occurring in more than 90% of all courses. Two patients died of sepsis during granulocytopenia. Three prognostic subgroups could be distinguished: (1) patients progressing on initial chemotherapy, (2) patients relapsing within 12 months, and (3) patients with late relapses. The response rates for these groups were 52%, 60%, and 83%, and the median survival duration 12, 29, and 40+ months, respectively. In a nonrandomized comparison, the survival of patients who responded to two cycles of Dexa-BEAM and had additional cycles of Dexa-BEAM (n = 14) was not different from those responding patients who underwent HDCT/ABMT (n = 19). However, the power to detect a 20% survival difference was only 33% in this comparison. - Conclusion - Dexa-BEAM is an effective salvage treatment for patients with Hodgkin's disease who fail to respond to multidrug chemotherapy. Efficacy and toxicity are comparable to HDCT/ABMT and underline the need for prospective randomized trials to define better the role of HDCT with and without ABMT in these patients.